Taking sides : clashing issues on controversial issues in American history (Guilford, CT : Dushkin Pub. Group, 1985)
Contents.--.v.1. The colonial period to reconstruction.--v.2. Reconstruction to present.
Keywords: United States -- History; United States -- Historiography